PEMANFAATAN INTERACTIVE e-BOOK BERBASIS ANDROID UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Hebron Pardede; Parlindungan Sitorus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2021)
The covid-19 pandemic that struck the world has forced educational institutions to carry out distance learning both online and offline. The main problem in distance learning is the unstable internet network in some areas far from urban areas and the teaching materials are not interactive. As a result, student motivation to learn independently is very lacking which results in low learning achievement. This research is a classroom action research in an effort to improve student learning achievement and learning motivation in the numerical method course, where the teaching material used is an interactive e-book. The results showed that learning achievement increased and completed 100% and student learning motivation was in the very high category. Interactive e-books are very effective in overcoming unstable internet network problems, because they can be accessed without being connected to the internet.